How Much Longer?. Issue 2 (September 2016) - Ahrens, Mark Alexander; Sanio, David
Abstract: Unrelenting traffic, corrosion and weathering all take their toll on the prestressed steel used in bridge construction. Structural engineers use mathematical models to predict the progress of fatigue and therefore the useful life of these structures more accurately. The reliability of forecasts depends on the quality of the data and the accuracy of the methods used.